Cross-Sectional Survey of Sausage Consumers in Algeria: Prevalence and Risk Factors for Development of Food-Borne Illnesses and Antibiotic Use Behavior - Hachemi, Amina; Mimoune, Nora; Boukhechem, Said; Zenia, Safia; Zaidi, Sara; Ait-Oudhia, Khatima; Khelef, Djamel (International Journal of Bio-resource and Stress Management, 2023)
This cross-sectional questionnaire study was designed to determine the prevalence of food-borne illnesses and potential risk factors among Algerian sausage consumers, and to assess antibiotics use behavior among sick consumers. From August, 2018 to June, 2019, a total of 800 structured questionnaires were distributed randomly to sausage consumers from ten (10) departments of Algiers, Algeria. The data collected were analyzed with different statistical approaches. The results showed that out of the 384 sausage consumers surveyed, 22.39% reported having food-borne illnesses after sausage consumption, with 8.14% of sick consumers hospitalized. The prevalence of foodborne illnesses among sausage consumers was significantly higher among males (25.69%) than females (21.09%) (OR=1.36), and also significantly higher (p<0.01) among consumers without children (24.54%) than among those who had children (17.12%). Sausage consumers who were immuno-deficient had the highest frequency of being sick, 41.38% (OR=3.62, p<0.0001), followed in descending order by consumers who had children, 34.85% (OR=1.9, p=0.01), and pregnant consumers, 28.12% (OR=1.56, p=0.03). For antibiotic use behavior, out of 86 sick consumers, 59.3% had self-medicated on antibiotics, and 17.44% had interrupted the antibiotics treatment. This study provides for the first-time information about baseline of the attitude and behavior regarding antibiotic use among Algerian sausage consumers who developed food-borne illness. Thus, it can be concluded that raw sausage must be consumed with precaution for vulnerable groups at risk. Public education programs should be developed to target misconceptions of antibiotics use and vulnerable groups at risk.